Identification of Agricultural Sector Base Areas in West Sumatra Using the Location Quotient - Andreas Sitanggang; Ari Muhammad Fajri (PT Bukuloka Literasi Bangsa, 2026)
This study aims to identify agricultural sector base areas in West Sumatra Province using the Location Quotient (LQ) approach (study for 2018-2023). The research applies a descriptive quantitative method using secondary data from Gross Regional Domestic Product (GRDP) by sector at the district and city levels during the period of 2018-2023. The results show that most districts have LQ values above 1, indicating that agriculture remains a base sector, while cities tend to have LQ values below 1, reflecting a more limited role of agriculture. Districts such as Pasaman, Kepulauan Mentawai, and Pasaman Barat consistently show relatively high and stable LQ values. Overall, changes in LQ values are relatively small, suggesting that the role of the agricultural sector has remained stable during the period of 2018-2023. Keywords: Location Quotient, agriculture sector, regional economy, base sector, West Sumatra